Hypothalamic involvement and the role of progesterone in the NGF-induced LH surge pathway. Issue 2 (8th July 2021) - Carrasco, Rodrigo A; Leonardi, Carlos E; Pezo, Sergio; Adams, Gregg P
Abstract : To elucidate the mechanism by which nerve growth factor (NGF) influences the LH secretory pathway in camelids, a series of experiments were done to determine the involvement of the hypothalamus (Experiment 1), the role of GnRH neurons (Experiment 2), and the effect of progesterone (Experiment 3) on the NGF-induced LH surge and ovulation in llamas. In Experiment 1, the declining phase of the NGF-induced LH surge was used to determine if the decline is a result of pituitary depletion or hypothalamic unresponsiveness. Female llamas were treated with NGF and, 7 h later, assigned to three groups and given a second dose of NGF ( n = 5), a dose of GnRH ( n = 5), or saline ( n = 6). The LH response was attenuated after the second dose of NGF vs GnRH. In Experiment 2, Fos expression (marker of neuronal activation) in GnRH neurons was examined in the hypothalamus of llamas after NGF or saline treatment ( n = 3 per group). Despite an LH surge in the NGF group but not in the saline group, no differences were detected between groups in Fos/GnRH co-expression. In Experiment 3, llamas in low-, medium-, and high-plasma progesterone groups ( n = 4 per group) were treated with NGF. The NGF-induced LH surge did not differ among treatment groups. Results from the present study show that the induction of a preovulatory LH surge by NGF may be controlled by a novel pathway involving GnRH neuro-terminals downstream of the hypothalamus and is independent of progesterone influence.